Tied-array beam localization of radio transients and pulsars. Issue 1 (7th March 2023) - Bezuidenhout, M C; Clark, C J; Breton, R P; Stappers, B W; Barr, E D; Caleb, M; Chen, W; Jankowski, F; Kramer, M; Rajwade, K; Surnis, M
Abstract: Multi-element interferometers such as MeerKAT, which observe with high time resolution and have a wide field of view, provide an ideal opportunity to perform real-time, untargeted transient and pulsar searches. However, because of data storage limitations, it is not always feasible to store the baseband data required to image the field of a discovered transient or pulsar. This limits the ability of surveys to effectively localize their discoveries and may restrict opportunities for follow-up science, especially of one-off events like some fast radio bursts. Here, we present a novel maximum-likelihood estimation approach to localizing transients and pulsars detected in multiple MeerKAT tied-array beams at once, which we call tied-array beam localization, as well as a Python implementation of the method named SeeKAT . We provide real-world examples of SeeKAT 's use as well as a Monte Carlo analysis to show that it is capable of localizing single pulses detected in beamformed MeerKAT data to (sub)arcsec precision.